2020
DOI: 10.1101/2020.05.18.101840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mrr1 regulation of methylglyoxal catabolism and methylglyoxal-induced fluconazole resistance inCandida lusitaniae

Abstract: 22In Candida species, the transcription factor Mrr1 regulates azole resistance genes in addition to the 23 expression of a suite of other genes including known and putative methylglyoxal reductases. 24Methylglyoxal (MG) is a toxic metabolic byproduct that is significantly elevated in certain disease states 25 that frequently accompany candidiasis, including diabetes, kidney failure, sepsis, and inflammation. 26Through the genetic analysis of Candida lusitaniae (syn. Clavispora lusitaniae) strains with differen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Constitutively active Mrr1 also appears to repress expression of 42 genes (fold change ≥ 1.5, FDR<0.05), including multiple iron and/or copper transporters and reductases, and sugar transporters (Table S1). These data combined with Bierman et al, which showed that C. lusitaniae Mrr1 is induced by the spontaneously formed stress signal methylglyoxal (33), imply that Mrr1 may play a larger role in a generalized metabolic or stress response, beyond what has been previously studied in response to FLZ and xenobiotic stressors.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Constitutively active Mrr1 also appears to repress expression of 42 genes (fold change ≥ 1.5, FDR<0.05), including multiple iron and/or copper transporters and reductases, and sugar transporters (Table S1). These data combined with Bierman et al, which showed that C. lusitaniae Mrr1 is induced by the spontaneously formed stress signal methylglyoxal (33), imply that Mrr1 may play a larger role in a generalized metabolic or stress response, beyond what has been previously studied in response to FLZ and xenobiotic stressors.…”
Section: Discussionsupporting
confidence: 54%
“…The expression of MGD1 and MGD2, two C. lusitaniae genes shown to be Mrr1-regulated, correlated with the expression of MDR1 ( Fig. 1D and Table S1) (10,13,33). Gene expression differences between U04 (MRR1 Y813C ), U04 mrr1∆, and U04 mrr1Δ +MRR1 Y813C found that mrr1∆ is fully complemented upon return of MRR1 Y813C to the native locus ( Fig.…”
Section: Naturally Evolved C Lusitaniae Mrr1 Alleles Confer Altered mentioning
confidence: 87%
See 1 more Smart Citation
“…However, fructose has been described to also be metabolized to a toxic glycolytic byproduct called methylglyoxal (MG), the elevated levels of which are responsible for hepatotoxicity in diabetic patients [ 40 ]. In Candida lusitaniae , the MG metabolism is believed to be mediated by Mgd1 and Mgd2 reductases, the expression of which is controlled by Mrr1p, which, in turn, is inducible by MG [ 41 ]. The homologous protein in C. albicans ( Ca Mrr1p) is a major transcriptional inductor of MDR1 [ 42 ].…”
Section: Resultsmentioning
confidence: 99%